Republic of Tajikistan : Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Request for a Waiver of Performance Criterion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
Discussions on the Second Review Under the Poverty Reduction and Growth Ffacility (PRGF) arrangement took place in Dushanbe. The IMF-supported program concentrates on enhancing macroeconomic stability and implementing structural reform in the key areas of banking, energy, and agriculture. The discussions also focused on improving the implementation of monetary policy, accelerating structural reform, and strengthening governance. The authorities plan to work with independent third parties to enhance the transparency of the farm-restructuring process. The continued strong growth of GDP is welcomed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet